Effect of Preheating on Microhardness, Degree of Conversion, and Depth of Cure of Various Bulk-Fill Composites - Berna Tarım; Zeynep Hale Keleş (Selcuk Dental Journal)
Background: This study aims to evaluate the effect of preheating on microhardness, degree of conversion, and depth of cure of bulk-fill composites (Tetric EvoCeram Bulk-Fill, SonicFill2) and a conventional composite (Tetric EvoCeram). Methods: Layers of Tetric EvoCeram (2 mm), Tetric EvoCeram Bulk-Fill (4 mm), and SonicFill2 (5 mm) were placed in 4-mm diameter molds and polymerized at room temperature or heated to 55oC for 10 s with a total number of 60 samples. Then, the top surfaces of samples were polished. 30 samples’ Vickers microhardness was measured from the top and bottom surfaces. The other 30 samples were pulverized into a fine powder, and the composites’ degree of conversion was measured with attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy. Obtained data were analyzed statistically with a significance level of p<0.05. Results: The degree of conversion of Tetric EvoCeram was higher than the minimum rate of clinically acceptable value, which is 55%, but the scores of Tetric EvoCeram Bulk-Fill and SonicFill2 were below the threshold. Preheating increased the degree of conversion of Tetric EvoCeram Bulk-Fill and SonicFill2. In addition, preheating did not affect depth of cure of SonicFill2 but decreased the rate of Tetric EvoCeram Bulk-Fill. Conclusion: The results showed that the effect of preheating on the degree of conversion and depth of cure varied according to the material. Keywords: Preheating, bulk-fill composite, degree of conversion, depth of cure, microhardness.